Corrosion behavior of low-alloy steel in Xinjiang's arid atmosphere: Divergent protective effects of Cr and Mn - Tao Wang; SiWei Zhang; ShenRong Lu; Cuiwei Du; Xiaogang Li (Journal of Materials Research and Technology, 2025)
Through systematic long-term atmospheric exposure, the corrosion performance and protective mechanisms of rust layers on low-alloy structural steels in Xinjiang's arid climate were comprehensively evaluated. Results demonstrate that MnO2 and MnFe2O4 can moderately enhance the compactness of the rust layer. However, the combined effects of strong wind-sand erosion and high diurnal temperature variations induce significant internal stresses within the rust layer, leading to crack formation. Notably, Cr alloying demonstrates superior corrosion mitigation effects through dual mechanisms: (1) catalytically facilitating the preferential formation of thermodynamically stable α-FeOOH, (2) generation of highly protective (FeCr2O4), Cr(OH)3 and Cr2O3.